Decomposition and Nutrient Release Dynamics of Ficus benghalensis L. Litter in Traditional Agroforestry Systems of Karnataka, Southern India. (4th March 2013) - Dhanya, B.; Viswanath, Syam; Purushothaman, Seema
Abstract : Decomposition and nutrient release dynamics of leaf litter of Ficus benghalensis, a common agroforestry species in southern dry agroclimatic zone of Karnataka, were studied using the standard litter bag technique in surface and subsurface methods of application. Results revealed a marginally higher rate of decay in subsurface placement (22.5% of initial litter mass remaining after one year of decomposition) compared to surface treatment (28.3% of initial litter mass remaining). Litter quality (lignin content and lignin/N ratio) and climatic and soil conditions of the study site (monthly rainfall and soil moisture) were found to influence the rate of decomposition. Mineralisation of litter was found to be in the order K > N > P. The paper further discusses the implications of these results for rainfed farming in Mandya and emphasises the potential of F. benghalensis in reducing nutrient input costs for resource-poor dryland farmers.